A high temperature resistant swelling tape for lithium battery and preparation method thereof

By using a base film with a three-layer composite film structure and applying adhesive, the problem of swelling tape for lithium batteries is easily shrinkable at high temperatures, high temperature stability and good swelling performance are achieved, and the life of lithium batteries is extended.

CN118995071BActive Publication Date: 2025-02-28ANHUI JUMEI BIOLOGICAL TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411328616.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-28
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

Existing swelling tape for lithium batteries is prone to shrink at high temperatures, causing battery deformation, affecting battery life, and low temperature resistance, which cannot meet the requirements for use under high temperature conditions.

Method used

A base film with a three-layer composite film structure is adopted, the intermediate layer is polycarbonate polyurethane, and the outer layer and the inner layer are materials with good film formation. The base film is cast through a three-layer coextrusion caster, and adhesive is applied to the inner layer side to form a high-temperature resistant swelling tape.

Benefits of technology

The swelling tape does not show obvious shrinkage and deformation under high temperature conditions, and has good swelling performance in the thickness direction, which can effectively fill the gap between the lithium battery cell and the shell, extend the battery life, and has high temperature stability and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 7EREHKV4N7HDPWITEHJNFOKFAMJZ6U89FRRIPAWI
    Figure 7EREHKV4N7HDPWITEHJNFOKFAMJZ6U89FRRIPAWI
  • Figure FDTGFCFJ5V7L8LGVNC5VGL4YUE9ABGP6D64RJH4H
    Figure FDTGFCFJ5V7L8LGVNC5VGL4YUE9ABGP6D64RJH4H
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium ion batteries, and specifically relates to a high temperature resistant swelling tape for lithium batteries and a preparation method thereof. It comprises a substrate film and an adhesive composite; the substrate film is a three-layer composite film consisting of an outer layer, an intermediate layer and an inner layer; the outer layer is composed of 75-95wt% polyethylene terephthalate-1,4-cyclohexane dimethanol copolymer and 5-25wt% of a compatibilizer; the intermediate layer is a polycarbonate type polyurethane; the inner layer is composed of 70-90wt% ethylene-acrylate copolymer and 10-30wt% of a compatibilizer. After the swelling tape obtained by the present invention is soaked in an electrolyte, there will be no obvious shrinkage deformation in the length and width directions, and it has good swelling performance in the thickness direction, can effectively fill the gap between the lithium battery core and the shell, can withstand high temperatures, has stable ingredients, high safety performance, and long battery life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a high temperature resistant swelling tape for lithium batteries and a preparation method thereof. Background Art

[0002] Cylindrical lithium batteries have been widely used in production due to their mature manufacturing process, high degree of automation, and convenience for standardized production. During the installation of cylindrical lithium batteries, a certain gap must be reserved between the battery cells and the shell in order to smoothly install the battery cells into the shell. During the use of the battery, shaking and vibration often occur. Due to the existence of these expansion gaps, with frequent shaking and vibration, it is very easy to cause the bare lithium battery cells and the shell to move relative to each other, resulting in damage to the electrode sheet, battery short circuit, increased resistance and other problems, thereby affecting the performance of the lithium battery and causing great safety hazards.

[0003] To solve this problem, the existing method is to wrap and bond a tape with a swelling function on the battery cell. When the battery cell wrapped with the swelling tape is assembled, there is still a certain gap, but when the tape contacts the electrolyte, it will swell and fill the entire gap, thereby fixing the battery cell and resisting external impact. This greatly improves the safety performance and service life of the battery.

[0004] The solutes in the electrolyte are generally lithium-containing materials such as lithium hexafluorophosphate. They are very afraid of water and will undergo violent decomposition reactions when in contact with water, thus affecting the efficacy and life of the battery. Therefore, the swelling tape is generally dried at about 110°C for 2 hours before use to avoid moisture from entering the battery as much as possible and causing adverse effects. Therefore, the swelling tape is required to be resistant to high temperatures.

[0005] CN111995957A discloses a directional polystyrene swelling tape with a high expansion ratio and a preparation method thereof. The swelling tape is composed of a single-sided release directional polystyrene film substrate and an acrylate adhesive layer. Although the swelling ratio is high, the swelling of the tape is mainly achieved by the microscopic holes generated by directional stretching to adsorb electrolyte solvents. The directional stretched film is prone to shrinkage in the width direction at high temperatures, thereby affecting the assembly gap and easily causing battery deformation. In addition, the tape has low temperature resistance and is not resistant to high temperatures. After drying, it shrinks at high temperatures and cannot be used.

[0006] CN 114213983 A discloses a base film of a swelling tape for lithium batteries and a swelling tape for lithium batteries, which can swell at a high rate in the area direction, have a high swelling rate in the length and width directions, and have average swelling performance in the thickness direction. Swelling deformation in the length and width directions may cause deformation of the battery, thereby affecting the battery life.

[0007] CN 115717038A discloses a high temperature resistant swellable adhesive tape, comprising a base layer and a pressure sensitive adhesive layer, wherein the material used to form the base layer is thermoplastic polyurethane with a Shore hardness of not less than 70D. However, after contacting the electrolyte, the swellable adhesive tape can only swell in the length and width direction, but not in the thickness direction, which is not conducive to filling the gap, and the swelling deformation in the length and width direction may cause deformation of the battery, thereby affecting the battery life.

[0008] CN111518481A discloses a special swelling tape for lithium batteries and its manufacturing process. The swelling tape includes a base layer and a coated pressure-sensitive adhesive layer. The base layer is composed of substances such as TPU, EVA, styrene resin solution and titanium dioxide. After the swelling tape contacts the electrolyte, it can only swell in the length and width directions, but cannot swell in the thickness direction, which is not conducive to filling the gap. Moreover, the titanium dioxide may overflow from the tape after swelling and enter the electrolyte, which poses a risk of contaminating the electrolyte and affecting the battery performance.

[0009] It can be seen that the existing swelling tape has a large swelling deformation in the length and width directions, but cannot swell in the thickness direction or the swelling rate in the thickness direction is low, which is not conducive to filling the gap and easily causes a series of problems such as battery deformation and affecting battery life. Summary of the invention

[0010] The purpose of the present invention is to provide a high-temperature resistant swelling tape for lithium batteries. After being soaked in electrolyte, the swelling tape will not show obvious shrinkage deformation in the length and width directions, has good swelling performance in the thickness direction, can effectively fill the gap between the lithium battery core and the shell, and does not affect the battery life. It can withstand high temperatures, has stable components, high safety performance, and long battery life. The present invention also provides a preparation method thereof.

[0011] The present invention provides a high temperature resistant swelling tape for lithium batteries, which is composed of a base film and an adhesive; the base film is a three-layer composite film consisting of an outer layer, an intermediate layer and an inner layer;

[0012] The outer layer is composed of 75-95wt% of polyethylene terephthalate-ethylene glycol-1,4-cyclohexane dimethanol ester copolymer and 5-25wt% of a compatibilizer;

[0013] The middle layer is polycarbonate polyurethane;

[0014] The inner layer is composed of 70-90 wt % of ethylene-acrylate copolymer and 10-30 wt % of compatibilizer.

[0015] Preferably, the preparation method of the polycarbonate polyurethane is: polycarbonate diol, ethylene glycol and a catalyst are mixed and stirred, and then reacted and extruded with diisocyanate through a twin-screw extruder to obtain the polycarbonate polyurethane.

[0016] Preferably, the polycarbonate diol is polyhexane carbonate diol with an average molecular weight of 1000. The higher the molecular weight of the polycarbonate diol, the longer the chain segment of polycarbonate in the polyurethane, and the higher the risk of dissolution in the electrolyte. The lower the molecular weight of the polycarbonate diol as a soft segment, the worse the toughness of the obtained polyurethane. The polyhexane carbonate diol is preferably ETERNACOLL TM UH-100.

[0017] Preferably, the weight ratio of the polycarbonate diol, ethylene glycol and diisocyanate added is 55:7-10:28-36.

[0018] Preferably, the catalyst is dibutyltin dilaurate catalyst; and the diisocyanate is hexamethylene diisocyanate.

[0019] As we all know, the function of the swelling tape is to wrap around the battery cell of the lithium battery. After being soaked in electrolyte, it fills the assembly gap between the battery cell and the shell through the expansion function generated by swelling. Therefore, only swelling in the thickness direction is really needed for battery assembly; while swelling in the length and width directions may cause deformation of the battery, thereby affecting the battery life.

[0020] The swelling tape mainly consists of two parts: a substrate film and an adhesive. The swelling is contributed by the substrate film, so the swelling ratio, whether it dissolves at high temperature, whether it expands in the thickness direction, whether it shrinks and deforms, etc. are all closely related to the substrate film. Therefore, the innovation of the present invention lies in how to design and manufacture a substrate film that can withstand high temperatures, does not have the problem of high-temperature shrinkage and deformation, and after being soaked in electrolyte, will not have obvious shrinkage and deformation in the length and width directions, has good swelling performance in the thickness direction, stable composition, and high safety performance.

[0021] The present invention makes the substrate film into a three-layer composite structure, the middle layer is polycarbonate polyurethane, which mainly plays a swelling function. The outer layer and the inner layer are both materials with good film-forming properties. The outer layer and the inner layer serve as protective layers, mainly playing the role of protecting the middle layer, further limiting the expansion of the substrate film in the length and width directions, and reducing the risk of dissolution of the substrate film, because the swelling rate will drop a lot after dissolution, thereby playing the role of increasing the swelling rate.

[0022] The present invention adopts polycarbonate polyurethane as the middle layer. The electrolyte of the lithium battery is mainly composed of electrolyte solvent and solute, the electrolyte solvent mainly includes ethylene carbonate, propylene carbonate, diethyl carbonate, etc., and the solute mainly includes lithium hexafluorophosphate, etc. Since there are a large number of carbonate segments and urethane bonds on the molecular chain of polycarbonate polyurethane, the structure of some segments is similar to that of dimethyl carbonate, ethylene carbonate, propylene carbonate, etc. in the electrolyte, and similar dissolves. Polycarbonate polyurethane has good compatibility with the electrolyte and has a large polarity. It is close to the solubility parameter and polarity of the electrolyte solvent, can absorb and swell well, thereby producing a greater swelling effect and improving the swelling performance.

[0023] Preferably, the compatibilizer in the outer layer is ethylene-acrylate-glycidyl acrylate copolymer; the ethylene segment in ethylene-acrylate-glycidyl acrylate copolymer (EMG) mainly contributes to excellent processing performance and film-forming properties, the acrylate segment mainly contributes to excellent toughness, and the glycidyl acrylate segment mainly contributes to active epoxy groups, which can react with the terminal carboxyl groups on PETG and TPU, thereby increasing the compatibility of PETG in the outer layer material and the middle layer material, and can effectively avoid delamination of the outer layer and the middle layer. Preferably, the content of glycidyl acrylate (GMA) in ethylene-acrylate-glycidyl acrylate copolymer is 6~19wt%, which has the best effect, and LOTADER is more preferred. TM AX8700, AX8750, AX8840, AX8900, AX8930, IGETBOND TM BF-2C, BF-E, BF-7M, CG5001, CG5004, ELVALOY TM PTW,4170.

[0024] Preferably, the ethylene-acrylate copolymer is one or more of ethylene-methyl acrylate, ethylene-ethyl acrylate, and ethylene-butyl acrylate.

[0025] The ethylene segment (EMA) in the ethylene-acrylate copolymer mainly contributes to excellent processing performance and film-forming properties, and the acrylate segment (such as methyl acrylate, ethyl acrylate, butyl acrylate) mainly contributes to excellent toughness. At the same time, the acrylate segment has good compatibility with the carbonate segment and urethane segment on TPU. Therefore, the inner layer material EMA has good compatibility with the middle layer material TPU. Preferably, the acrylate content in the ethylene-acrylate copolymer is 24-35wt%, and the ethylene-acrylate copolymer is preferably LOTRYL TM24MA02T, 24MA07T, 29MA03T, 28BA175T, 28BA700T, 35BA40T, 35BA320T, ELVALOY™ AC 1125, AC 12024S, AC 1224, AC 1330, AC 34035, AC3427.

[0026] Preferably, the compatibilizer in the inner layer is ethylene-acrylate-maleic anhydride copolymer. In order to further improve the compatibility between the inner layer material EMA and the middle layer material TPU, we added the compatibilizer ethylene-acrylate-maleic anhydride copolymer (EMH) to the inner layer material. Compared with EMA, EMH only has more maleic anhydride groups on the molecular chain, so the compatibility between EMH and EMA is very good. The maleic anhydride groups on EMH can react with the terminal hydroxyl groups on the TPU molecules, thereby further enhancing the compatibility between EMA and TPU, and can effectively avoid the delamination of the inner layer and the middle layer.

[0027] At the same time, the acrylate segments and maleic anhydride groups on EMA and EMH make the inner layer material highly compatible with acrylate adhesives, which is beneficial for coating the substrate film with adhesive to prepare a swelling tape.

[0028] Preferably, the content of maleic anhydride (MAH) in the ethylene-acrylate-maleic anhydride copolymer is 2.8-3.6 wt %, which has the best effect, and LOTADER is more preferred. TM 4210, 3210, 3410, 3430, LX4110, 5500, 6200, HX8290, 8200, TX8030.

[0029] Preferably, the molar ratio of 1,4-cyclohexanedimethanol to ethylene glycol in the polyethylene terephthalate-ethylene glycol-1,4-cyclohexanedimethanol ester copolymer (PETG) is 20-50:50-80. When the molar ratio of 1,4-cyclohexanedimethanol (CHDM) to ethylene glycol (EG) is lower than 20:80, the melting point of the copolymer is relatively high, which is quite different from the processing temperature of TPU and is not suitable for co-extrusion with TPU to form a film; when the molar ratio of CHDM to EG is higher than 20:80, the melting point of the copolymer gradually decreases. The lower the CHDM content, the lower the processing temperature, and it is suitable for co-extrusion with TPU to form a film. Moreover, the higher the CHDM content, the better the toughness of the copolymer, the better the melt strength, and the easier it is to form a film. When the molar ratio of CHDM to EG is higher than 50:50, the EG segments in the copolymer gradually decrease, and the CHDM segments gradually increase. The molecular structure of the EG segments is similar to that of the electrolyte solvent, and the compatibility is good. The fewer the EG segments, the worse the affinity between the electrolyte and the copolymer, and it is more difficult for the electrolyte to penetrate the copolymer to reach the polyurethane middle layer. Polyethylene terephthalate-ethylene glycol-1,4-cyclohexane dimethanol ester copolymer is preferably SKYGREENTM K2012, ESTAR TM GN077, ESTAR TM MN200, Hualei TM CR5511 or Hualei TM CR5083.

[0030] Preferably, the thickness ratio of the outer layer, the middle layer and the inner layer of the three-layer composite film is 1-1.5:4:1-1.5.

[0031] The present invention also provides a method for preparing the above-mentioned high temperature resistant swelling tape for lithium batteries, comprising the following steps:

[0032] (1) Outer layer material: polyethylene terephthalate-ethylene glycol-1,4-cyclohexane dimethanol copolymer and compatibilizer ethylene-acrylate-glycidyl acrylate copolymer, stir and mix well;

[0033] (2) Inner layer material: Weigh ethylene-acrylate copolymer and compatibilizer ethylene-acrylate-maleic anhydride copolymer, stir and mix well;

[0034] (3) Intermediate layer material: polycarbonate diol, ethylene glycol and a catalyst are mixed and stirred, and then added into a twin-screw extruder with diisocyanate for reaction extrusion, pelletization and drying to obtain the polycarbonate polyurethane;

[0035] (4) adding the outer layer material, the middle layer material and the inner layer material into corresponding extruders respectively, and obtaining a three-layer composite film by a three-layer co-extrusion casting method, namely, a substrate film;

[0036] (5) An adhesive is applied on the inner layer material side of the substrate film to obtain the high temperature swelling resistant adhesive tape for lithium battery.

[0037] Wherein, in step (3), the stirring temperature is 60-70°C, the stirring time is 3-4 hours, and the reaction extrusion temperature is 190-210°C.

[0038] The present invention utilizes a three-layer co-extrusion casting machine to cast a substrate film. The three-layer co-extrusion casting machine has three independent single-screw extruders. The outer layer material, the middle layer material and the inner layer material are respectively added to the corresponding extruders, and then cast under heating to obtain a substrate film with a three-layer composite structure.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] (1) After being soaked in electrolyte, the swelling tape prepared by the present invention will not show obvious shrinkage deformation in the length and width directions, and has good swelling performance in the thickness direction. The swelling rate at 45°C is above 350%, and the swelling rate at 85°C is above 430%. After swelling, it can effectively fill the assembly gap between the lithium battery cell and the shell; and it will not cause battery deformation, and the battery life is long.

[0041] (2) The substrate film prepared by the present invention is resistant to high temperatures and will not show obvious shrinkage deformation in the length and width directions under high temperature conditions, and has stable high temperature performance.

[0042] (3) The composition of the present invention is stable, there is no problem of electrolyte contamination due to overflow from the tape, and the safety performance is high. DETAILED DESCRIPTION

[0043] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.

[0044] The main sources of raw materials are as follows:

[0045] Polyethylene glycol carbonate glycol was from Ube Kosan Co., Ltd., Japan;

[0046] Dibutyltin dilaurate was from Nantong Aidewang Chemical Co., Ltd.;

[0047] Hexamethylene diisocyanate comes from Wanhua Chemical Group.

[0048] The equipment parameters of the three-layer co-extrusion casting machine used in the specific embodiment of the present invention are as follows: the screw diameter of the outer layer extruder is 55mm, the aspect ratio is 30:1; the screw diameter of the middle layer extruder is 65mm, the aspect ratio is 30:1; the screw diameter of the outer layer extruder is 55mm, the aspect ratio is 30:1, the die head width is 1200mm, and the die gap is 2mm.

[0049] Example 1

[0050] A method for preparing a high temperature resistant swelling tape for a lithium battery comprises the following steps:

[0051] (1) Outer layer material: Weigh 85 kg of polyethylene terephthalate-ethylene glycol-1,4-cyclohexane dimethanol ester copolymer (ESTAR TM GN077) and 15kg ethylene-acrylate-glycidyl acrylate copolymer (LOTADER TM AX8900, GMA content 8wt%), stir and mix well and set aside.

[0052] (2) Inner layer material: Weigh 80 kg of ethylene-methyl acrylate copolymer (ELVALOY™ AC 1224, methyl acrylate content 24 wt%) and 20 kg of ethylene-acrylate-maleic anhydride copolymer (LOTADER TM 4210, MAH content 3.6wt%), and stir to mix well and set aside.

[0053] (3) Middle layer material: 55 kg of polyhexane carbonate diol (ETERNACOLL TM UH-100, average molecular weight 1000), 10kg ethylene glycol (EG) and 0.01kg dibutyltin dilaurate catalyst, stirred at 60°C for 4 hours to obtain a prepared polyester polyol, then the prepared polyester polyol and 36kg hexamethylene diisocyanate (HDI) were added into a twin-screw extruder through a feeding and perfusion system, and reaction extrusion was carried out at 200°C (main engine speed 200r / min), pelletized, and dried to obtain a polycarbonate polyurethane, which is the middle layer material;

[0054] (4) adding the outer layer material, the middle layer material and the inner layer material into the corresponding extruders respectively, the temperature of each zone of the outer layer machine is 160-170-180-190°C, the temperature of each zone of the middle layer machine is 150-170-180-190°C, the temperature of each zone of the inner layer machine is 140-150-160-170°C, the temperature of the connector is 200°C, the temperature of the die head is 190°C, and a three-layer composite film is obtained by casting through a three-layer co-extrusion casting machine. The thickness ratio of the three-layer film is outer layer: middle layer: inner layer = 1.5:4:1, and the film thickness is 0.051 mm, which is the substrate film;

[0055] (5) Applying an adhesive on one side of the inner layer material of the substrate film to obtain the high temperature swelling resistant adhesive tape for lithium battery; the adhesive is a conventional commercial product in the art.

[0056] The substrate film obtained in step (4) was cut into 40*30 mm for testing.

[0057] Example 2

[0058] A method for preparing a high temperature resistant swelling tape for a lithium battery comprises the following steps:

[0059] (1) Outer layer material: Weigh 95 kg of polyethylene terephthalate-ethylene glycol-1,4-cyclohexane dimethanol ester copolymer (ESTAR TM MN200) and 5kg ethylene-acrylate-glycidyl acrylate copolymer (IGETBOND TM CG5004, GMA content 19wt%), stir and mix well and set aside.

[0060] (2) Inner layer material: weigh 90 kg of ethylene-butyl acrylate copolymer (LOTRYL TM 35BA40T, butyl acrylate content 35wt%) and 10kg ethylene-acrylate-maleic anhydride copolymer (LOTADER TM 3430, MAH content 3.1wt%), and stir to mix well and set aside.

[0061] (3) Middle layer material: 55 kg of polyhexane carbonate diol (ETERNACOLL TM UH-100, average molecular weight 1000), 8kg ethylene glycol (EG) and 0.01kg dibutyltin dilaurate catalyst, stirred at 70°C for 3 hours to obtain a prepared polyester polyol, then the prepared polyester polyol and 30.5kg hexamethylene diisocyanate (HDI) were added into a twin-screw extruder through a feeding and perfusion system, and reaction extrusion was carried out at 210°C (main engine speed 200r / min), pelletized, and dried to obtain a polycarbonate polyurethane, which is the middle layer material;

[0062] (4) adding the outer layer material, the middle layer material and the inner layer material into the corresponding extruders respectively, the temperature of each zone of the outer layer machine is 160-170-180-190°C, the temperature of each zone of the middle layer machine is 150-160-170-180°C, the temperature of each zone of the inner layer machine is 140-150-160-170°C, the temperature of the connector is 190°C, the temperature of the die head is 180°C, and a three-layer composite film is obtained by casting through a three-layer co-extrusion casting machine. The thickness ratio of the three-layer film is outer layer: middle layer: inner layer = 1.5:4:1, and the film thickness is 0.052 mm, which is the substrate film;

[0063] (5) Applying an adhesive on one side of the inner layer material of the substrate film to obtain the high temperature swelling resistant adhesive tape for lithium battery; the adhesive is a conventional commercial product in the art.

[0064] The substrate film obtained in step (4) was cut into 40*30 mm for testing.

[0065] Example 3

[0066] A method for preparing a high temperature resistant swelling tape for a lithium battery comprises the following steps:

[0067] (1) Outer layer material: Weigh 75 kg of polyethylene terephthalate-1,4-cyclohexane dimethanol copolymer (SKYGREEN TM K2012) and 25kg ethylene-acrylate-glycidyl acrylate copolymer (IGETBOND TM BF-E, GMA content 12wt%), stir and mix evenly and set aside.

[0068] (2) Inner layer material: Weigh 70 kg of ethylene-methyl acrylate copolymer (ELVALOY™ AC 1330, methyl acrylate content 30 wt%) and 30 kg of ethylene-acrylate-maleic anhydride copolymer (LOTADER TM 3210, MAH content 3.1wt%), and stir to mix well and set aside.

[0069] (3) Middle layer material: 55 kg of polyhexane carbonate diol (ETERNACOLL TM UH-100, average molecular weight 1000), 9kg ethylene glycol (EG) and 0.01kg dibutyltin dilaurate catalyst, stirred at 65°C for 4 hours to obtain a prepared polyester polyol, then the prepared polyester polyol and 33.5kg hexamethylene diisocyanate (HDI) were added into a twin-screw extruder through a feeding and perfusion system, and reaction extrusion was carried out at 190°C (main engine speed 200r / min), pelletized, and dried to obtain a polycarbonate polyurethane, which is the middle layer material;

[0070] (4) adding the outer layer material, the middle layer material and the inner layer material into the corresponding extruders respectively, the temperature of each zone of the outer layer machine is 170-180-190-200°C, the temperature of each zone of the middle layer machine is 150-170-180-190°C, the temperature of each zone of the inner layer machine is 140-150-160-170°C, the temperature of the connector is 210°C, the temperature of the die head is 200°C, and a three-layer composite film is obtained by casting through a three-layer co-extrusion casting machine. The thickness ratio of the three-layer film is outer layer: middle layer: inner layer = 1:4:1.5, and the film thickness is 0.050 mm, which is the substrate film;

[0071] (5) Applying an adhesive on one side of the inner layer material of the substrate film to obtain the high temperature swelling resistant adhesive tape for lithium battery; the adhesive is a conventional commercial product in the art.

[0072] The substrate film obtained in step (4) was cut into 40*30 mm for testing.

[0073] Comparative Example 1

[0074] A high temperature resistant swelling tape for lithium battery, which is basically the same as Example 1, except that: polyhexane carbonate diol (ETERNACOLL TM UH-100, average molecular weight 1000) was replaced with poly(hexanediol adipate) diol (Meirui New Materials P1110, average molecular weight 1000) to obtain a substrate film with a thickness of 0.051 mm, which was cut into 40*30 mm for testing.

[0075] Comparative Example 2

[0076] A high temperature resistant swelling tape for lithium batteries is basically the same as Example 1, the only difference being that the outer layer and inner layer materials are replaced with the intermediate layer material prepared in Example 1 to obtain a substrate film with a thickness of 0.052 mm, which is cut into 40*30 mm for testing.

[0077] Comparative Example 3

[0078] A high temperature swelling resistant tape for lithium battery, which is basically the same as Example 1, except that the outer layer material is polyethylene terephthalate-ethylene glycol-1,4-cyclohexane dimethanol copolymer (ESTAR TM GN077) replaced by polystyrene (STYROLUTION TM PS 1540) to obtain a substrate film with a thickness of 0.050 mm, which was cut into 40*30 mm for testing.

[0079] Comparative Example 4

[0080] A high temperature resistant swelling tape for lithium battery is basically the same as Example 1, except that the outer layer material is 100% polyethylene terephthalate-ethylene glycol-1,4-cyclohexane dimethanol copolymer, that is, ethylene-acrylate-glycidyl acrylate copolymer is not added. The obtained composite film has a delamination phenomenon and cannot meet the use requirements.

[0081] Comparative Example 5

[0082] A high temperature resistant swelling tape for lithium battery is basically the same as Example 1, the only difference being that the inner layer material is 100% ethylene-acrylate copolymer, that is, no ethylene-acrylate-maleic anhydride copolymer is added. The obtained composite film has a delamination phenomenon and cannot meet the requirements of use.

[0083] Comparative Example 6

[0084] A high temperature resistant swelling tape for lithium batteries is basically the same as Example 1, the only difference being that the outer layer material compatibilizer is replaced by POE-g-GMA (Ningbo Energy Light, E533, GMA content 2.8~3.1wt%) from ethylene-acrylate-glycidyl acrylate copolymer; a substrate film with a thickness of 0.050 mm is obtained and cut into 40*30 mm for testing.

[0085] Comparative Example 7

[0086] A high temperature resistant swelling tape for lithium batteries is basically the same as Example 1, the only difference being that the inner layer material compatibilizer ethylene-acrylate-maleic anhydride copolymer is replaced with POE-g-MAH (Ningbo Nengzhiguang, MC509, MAH content 0.5~0.8wt%); a substrate film with a thickness of 0.051 mm is obtained and cut into 40*30 mm for testing.

[0087] The substrate films prepared in Examples 1 to 3 and Comparative Examples 1 to 3, 6 to 7 were cut into pieces of about 40*30 mm, and the following tests were performed respectively:

[0088] Swelling rate test method: The ratio of the size of the film after immersion in electrolyte to the size before immersion is the swelling rate or expansion rate.

[0089] Among them, the lithium battery electrolyte comes from Guangzhou Tianci High-tech Materials Co., Ltd. The electrolyte solvent composition is: ethylene carbonate: propylene carbonate: diethyl carbonate = 1:1:1 (volume ratio), and the solute is lithium hexafluorophosphate.

[0090] Shrinkage test conditions: 110℃, drying for 2h. Shrinkage calculation method: The difference between the length and width of the film after drying and the length and width before drying, and the ratio of the length and width before drying is the shrinkage.

[0091] After the substrate film obtained in Comparative Example 6 was soaked in an electrolyte at 45°C, the outer layer and the middle layer peeled off and delaminated, and the use requirements could not be met, so no other tests were performed; after the substrate film obtained in Comparative Example 7 was soaked in an electrolyte at 45°C, the inner layer and the middle layer peeled off and delaminated, and the use requirements could not be met, so no other tests were performed.

[0092] The test results of Examples 1-3 and Comparative Examples 1-3 are shown in Tables 1 and 2.

[0093]

[0094]

[0095] By comparing the data in Table 1 and Table 2, it can be seen that the substrate films prepared in Examples 1 to 3 did not show obvious shrinkage deformation in the length and width directions after drying at 110°C. Due to the protection of the protective layer, the shrinkage deformation of Comparative Example 1 was relatively small; although Comparative Example 2 did not have the protection of the outer and inner protective layers, it shrank; Comparative Example 3 replaced the outer layer material with PS material. PS is an amorphous material. Microscopically, the molecular chain exists in the form of a random coil. The glass transition temperature is 105°C. When dried and heated at 110°C, the molecular chain moves more actively, shrinks and deforms, and shrinks and deforms more. The thickness of Examples 1 to 3 and Comparative Examples 1 to 3 before and after drying is 0.052±0.002mm, and there is no obvious change in thickness before and after drying. It shows that the swelling tape of the present invention can withstand high temperatures.

[0096] At the same time, it can be seen from the data in Table 1 and Table 2 that after the substrate films prepared in Examples 1 to 3 are immersed in the electrolyte, the swelling rate in the length and width directions is not very large, and the swelling rate in the thickness direction is relatively high. The swelling rate at 45°C is above 350%, and the swelling rate at 85°C reaches above 430%. After swelling, they can fully fill the assembly gap. In Comparative Example 1, the swelling rate is significantly reduced at both 45°C and 85°C; in Comparative Example 2, after the outer layer and the inner layer are replaced by the middle layer, it is equivalent to that the three-layer structure becomes a one-layer structure. Without the protection of the inner and outer layers, the swelling rate at 45°C does not increase, but decreases. This shows that without the protection of the outer layer, partial dissolution occurs, and the dissolution is greater than the swelling, but the lack of dissolution is not apparent. However, obvious dissolution occurs at 85°C, and the dissolved part will no longer swell, and the swelling will naturally decrease a lot; in Comparative Example 3, the outer layer is replaced with PS material. Since the polarity of PS material is weak and its compatibility with the electrolyte is poor, it is difficult for the electrolyte to penetrate PS. Therefore, the swelling rate is not too high whether it is immersed at 45°C or 85°C.

Claims

1. A high temperature resistant swelling tape for lithium batteries, characterized in that: It is composed of a base film and an adhesive; the base film is a three-layer composite film consisting of an outer layer, a middle layer and an inner layer; The outer layer is composed of 75-95wt% of polyethylene terephthalate-ethylene glycol-1,4-cyclohexane dimethanol ester copolymer and 5-25wt% of a compatibilizer; The middle layer is polycarbonate polyurethane; The inner layer is composed of 70-90wt% ethylene-acrylate copolymer and 10-30wt% compatibilizer; The compatibilizer in the outer layer is ethylene-acrylate-glycidyl acrylate copolymer; the compatibilizer in the inner layer is ethylene-acrylate-maleic anhydride copolymer.

2. The high temperature swelling resistant adhesive tape for lithium battery according to claim 1, characterized in that: The preparation method of the polycarbonate polyurethane is as follows: polycarbonate diol, ethylene glycol and a catalyst are mixed and stirred, and then reacted and extruded with diisocyanate through a twin-screw extruder to obtain the polycarbonate polyurethane.

3. The high temperature swelling resistant adhesive tape for lithium battery according to claim 2, characterized in that: The polycarbonate diol is polyhexane carbonate diol, and the average molecular weight is 1000.

4. The high temperature swelling resistant adhesive tape for lithium battery according to claim 2, characterized in that: The added weight ratio of the polycarbonate diol, ethylene glycol and diisocyanate is 55:7-10:28-36; the catalyst is dibutyltin dilaurate catalyst; and the diisocyanate is hexamethylene diisocyanate.

5. The high temperature swelling resistant adhesive tape for lithium battery according to claim 1, characterized in that: The ethylene-acrylate copolymer is one or more of ethylene-methyl acrylate, ethylene-ethyl acrylate, and ethylene-butyl acrylate.

6. The high temperature swelling resistant adhesive tape for lithium battery according to claim 1, characterized in that: The molar ratio of 1,4-cyclohexanedimethanol to ethylene glycol in the polyethylene terephthalate-ethylene glycol-1,4-cyclohexanedimethanol copolymer is 20-50:50-80; The content of glycidyl acrylate in the ethylene-acrylate-glycidyl acrylate copolymer is 6-19wt%; The content of acrylate in the ethylene-acrylate copolymer is 24-35wt%; The content of maleic anhydride in the ethylene-acrylate-maleic anhydride copolymer is 2.8-3.6 wt %.

7. The high temperature swelling resistant adhesive tape for lithium battery according to claim 1, characterized in that: The thickness ratio of the outer layer, the middle layer and the inner layer of the three-layer composite film is 1-1.5:4:1-1.

5.

8. A method for preparing the high temperature resistant swelling tape for lithium battery according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Outer layer material: polyethylene terephthalate-ethylene glycol-1,4-cyclohexane dimethanol copolymer and compatibilizer ethylene-acrylate-glycidyl acrylate copolymer, stir and mix well; (2) Inner layer material: Weigh ethylene-acrylate copolymer and compatibilizer ethylene-acrylate-maleic anhydride copolymer, stir and mix well; (3) Intermediate layer material: polycarbonate diol, ethylene glycol and tin catalyst are mixed and stirred, and then added into a twin-screw extruder with diisocyanate for reaction extrusion, pelletization and drying to obtain the polycarbonate polyurethane; (4) adding the outer layer material, the middle layer material and the inner layer material into corresponding extruders respectively, and obtaining a three-layer composite film by a three-layer co-extrusion casting method, namely, a substrate film; (5) An adhesive is applied on the inner layer material side of the substrate film to obtain the high temperature swelling resistant adhesive tape for lithium battery.

9. The preparation method according to claim 8, characterized in that: In step (3), the stirring temperature is 60-70°C, the stirring time is 3-4 hours, and the reaction extrusion temperature is 190-210°C.

Citation Information

Patent Citations

  • Swelling adhesive tape special for lithium battery and manufacturing process thereof

    CN111518481A

  • High-expansion-ratio oriented polystyrene expansion adhesive tape and preparation method thereof

    CN111995957A

  • Composite film for wafer grinding and preparation method of film

    CN109825215A

  • Swelling adhesive tape base material, swelling adhesive tape and lithium battery

    CN117683218A